Development of an electronic breast pathology database in a community health system - Heidi D Nelson; Roshanthi Weerasinghe; Maritza Martel; Carlo Bifulco; Ted Assur; Joann G Elmore; Donald L Weaver (Elsevier, 2014)
Background: Health care systems rely on electronic patient data, yet access to breast tissue pathology results continues to depend on interpreting dictated free-text reports. Objective: The objective was to develop a method to electronically search and categorize pathologic diagnoses of patients' breast tissue specimens from dictated free-text pathology reports in a large health system for multiple users including clinicians. Design: A database integrating existing patient-level administrative and clinical information for breast cancer screening and diagnostic services and a web-based application for comprehensive searching of pathology reports were developed by a health system team led by pathologists. The Breast Pathology Assessment Tool and Hierarchy for Diagnosis (BPATH-Dx) provided search terms and guided electronic transcription of diagnoses from text fields on breast pathology clinical reports to standardized categories. Approach: Breast pathology encounters in the pathology database were matched with administrative data for 7332 women with breast tissue specimens obtained from an initial procedure in the health system from January 1, 2008 to December 31, 2011. Sequential queries of the pathology text based on BPATH-Dx categorized biopsies according to their worst pathological diagnosis, as is standard practice. Diagnoses ranged from invasive breast cancer (23.3%), carcinoma in situ (7.8%), atypical lesions (6.39%), proliferative lesions without atypia (27.9%), and nonproliferative lesions (34.7%), and were further classified into subcategories. A random sample of 5% of reports that were manually reviewed indicated 97.5% agreement. Conclusions: Sequential queries of free-text pathology reports guided by a standardized assessment tool in conjunction with a web-based search application provide an efficient and reproducible approach to accessing nonmalignant breast pathology diagnoses. This method advances the use of pathology data and electronic health records to improve health care quality, patient care, outcomes, and research.